On (Dang) Quesadillas and Nachos. Mexicans, Mexican-Americans, and Religion in the Films of Jared Hess On (Dang) Quesadillas and Nachos - David S. Dalton (Journal for Religion, Film and Media, 2019)
Across his cinema, the US, Mormon director Jared Hess has represented the Mexican Other in ambiguous ways that affirm the humanity of the US's southern neighbors while at the same time signaling them as irreconcilably different from-and perhaps simpler than-their North American counterparts. This holds especially true in Napoleon Dynamite (2004) and Nacho Libre (United States 2006), his two most commercially successful films. The Mexican protagonists of both movies win the audience's affection in part by playing to stereotypes that rigidly separate them from US culture at large. Mexico's oversized role in Hess's aesthetic is obvious even to the casual viewer; however, few critics have attempted to reconcile the director's combination of paternalism and solidarity with people from south of the US border. In this article, I argue that Hess's ambiguous representation of Mexican peoples and cultures reflects a type of "benevolent racism" that is common within white, North American Mormon communities who paradoxically view people of Mexican descent both as Others and as the physical and spiritual heirs of the peoples of the Book of Mormon.